Telemedicine networks for acute stroke: an analysis of global coverage, gaps, and opportunities - Tunkl, Christine; Agarwal, Ayush; Ramage, Emily; Velez, Faddi Saleh; Roushdy, Tamer; Ullberg, Teresa; Li, Linxin; Carbonera, Leonardo A; Yusof Khan, Abdul Hanif Khan; Ciopleias, Bogdan; Law, Zhe Kang; Katsanos, Aristeidis H; et al. (International journal of stroke, 2025)
Background: Despite the proven efficacy of telestroke in improving clinical outcomes by providing access to specialized expertise and allowing rapid expert hyperacute stroke management and decision-making, detailed operational evidence is scarce, especially for less developed or lower income regions. - Aim: We aimed to map the global telestroke landscape and characterize existing networks. - Methods: We employed a four-tiered approach to comprehensively identify telestroke networks, primarily involving engagement with national stroke experts, stroke societies, and international stroke authorities. A carefully designed questionnaire was then distributed to the leaders of all identified networks to assess these networks’ structures, processes, and outcomes. - Results: We identified 254 telestroke networks distributed across 67 countries. High-income countries (HICs) concentrated 175 (69%) of the networks. No evidence of telestroke services was found in 58 (30%) countries. From the identified networks, 88 (34%) completed the survey, being 61 (71%) located in HICs. Network setup was highly heterogeneous, ranging from 17 (22%) networks with more than 20 affiliated hospitals, providing thousands of annual consultations using purpose-built highly specialized technology, to 11 (13%) networks with fewer than 120 consultations annually using generic videoconferencing equipment. Real-time video and image transfer was employed in 64 (75%) networks, while 62 (74%) conducting quality monitoring. Most networks established in the past 3 years were located in low- and middle-income countries (LMICs). - Conclusion: This comprehensive global survey of telestroke networks found significant variation in network coverage, setup, and technology use. Most services are in HICs, and a few services are in LMICs, although an emerging trend of new networks in these regions marks a pivotal moment in global telestroke care. The wide variation in quality monitoring practices across networks, with many failing to report key performance metrics, underscores the urgent need for standardized, resource-appropriate, quality assurance measures that can be adapted to diverse settings.
Online verfügbar: 26. Oktober 2024
Gesehen am 04.06.2025